EFFECTIVENESS OF GROUP GUIDANCE SERVICES WITH CINEMATHERAPY METHOD TO INCREASE SELF-EFFICACY IN GUIDANCE AND COUNSELING STUDENTS CLASS OF 2020 PGRI UNIVERSITY BANYUWANGI: EFEKTIVITAS LAYANAN BIMBINGAN KELOMPOK DENGAN METODE CINEMATHERAPY UNTUK MENINGKATKAN SELF-EFFICACY PADA MAHASISWA BIMBINGAN DAN KONSELING ANGKATAN 2020 UNIVERSITAS PGRI BANYUWANGI - SITI ADRIYANI; Heriberthus Wicaksono; Ahmad Sulthoni (BIMBINGAN DAN KONSELING BANYUWANGI, 2024)
Students are individuals who are pursuing education in higher education. One of the problems that exists in the 2020 class of counseling guidance students at PGRI Banyuwangi University is low self-efficacy. The solution provided by the researcher is a group guidance service with the Cinematherapy method. In this service, research subjects are invited to discuss with group members and counselors to provide stimulus through motivational videos. The approach in this study uses a quantitative experiment designed as one group pretest-postest. This study had a population of 42 respondents and the research subjects were taken by 10 students who were in the low self-efficacy category. The percentage for pretest is 63.7% and the percentage for posttest is 98.5%. This can prove that group guidance services using Cinematherapy are effective in increasing self-efficacy in counseling guidance students of the Class of 2020 at PGRI Banyuwangi University.